Visual Outcomes of Immediate Versus Delayed Vitrectomy for Dropped Nucleus during Phacoemulsification - Syed Fawad Rizvi, Shakir Zafar, Syed Asaad Mahmood, Munira Shakir, Saima Amin (Pakistan Journal of Ophthalmology, 2016)
Purpose: To compare the visual outcome of patients undergoing immediate pars plana vitrectomy (PPV) surgery for dropped nucleus after phacoemulsification with visual outcomes in patients undergoing delayed PPV. Study Design: Retrospective quasi – experimental. Place and Duration of study: This study was conducted at LRBT Tertiary Eye Hospital, Karachi from February 2008 to February 2014. Material and Methods: Records of patients who underwent PPV for dislocated lens fragments were reviewed. Patients were divided into two groups depending on whether they underwent PPV immediately following nucleus drop (group A) or as a second procedure within 15 days’ time (group B). Data collected included patient demographics, pre- operative best-corrected visual acuity (BCVA), duration of follow up, post-operative intraocular pressure, final BCVA and post-operative complications. Patient data was analysed at 12 months post-operatively. IBM SPSS 21 was used for data analysis. Results: Fifty seven patients (30 in group A and 27 in group B) were included in this study. The mean postoperative BCVA at 12 months for group A was 6/12-1 (range 6/6 – 6/36) and for group B was 6/12 (range 6/6 – 6/36). The mean improvement seen in BCVA was by 4.83 ± 1.39 lines of Snellen chart in group A and 4.67 ± 1.94 lines in group B compared to the preoperative visual acuities (p-value = 0.709). Cystoid macular edema (CME) occurred in 16% (5 patients) in group A and 11% (3 patients) in group B while corneal edema was encountered in 7% (2 patients) in group A and 4% (1 patient) in group B. Conclusions: Although the final visual outcomes were comparable between the two groups, early vitrectomy reduces the morbidity and results in a quicker visual recovery. Key-words: Dropped nucleus; Lens Subluxation; Phacoemulsification; Posterior Capsular Rupture; Vitrectomy.